Early Childhood Education to Promote Health Equity: A Community Guide Economic Review. Issue 1 (January 2018) - Ramon, Ismaila; Chattopadhyay, Sajal K.; Barnett, W. Steven; Hahn, Robert A.
Abstract : Context: A recent Community Guide systematic review found that early childhood education (ECE) programs improve educational, social, and health-related outcomes and advance health equity because many are designed to increase enrollment for high-risk children. This follow-up economic review examines how the economic benefits of center-based ECE programs compare with their costs. Evidence Acquisition: Kay and Pennucci from the Washington State Institute for Public Policy, whose meta-analysis formed the basis of the Community Guide effectiveness review, conducted a benefit-cost analysis of ECE programs for low-income children in Washington State. We performed an electronic database search using both effectiveness and economic key words to identify additional cost-benefit studies published through May 2015. Kay and Pennucci also provided us with national-level benefit-cost estimates for state and district and federal Head Start programs. Evidence Synthesis: The median benefit-to-cost ratio from 11 estimates of earnings gains, the major benefit driver for 3 types of ECE programs (ie, state and district, federal Head Start, and model programs), was 3.39:1 (interquartile interval [IQI] = 2.48-4.39). The overall median benefit-to-cost ratio from 7 estimates of total benefits, based on all benefit components including earnings gains, was 4.19:1 (IQI = 2.62-8.60), indicating that for every dollar invested in the program, there was a return of 4.19 in total benefits. Conclusions: ECE programs promote both equity and economic efficiency. Evidence indicates there is positive social return on investment in ECE irrespective of the type of ECE program. The adoption of a societal perspective is crucial to understand all costs and benefits of ECE programs regardless of who pays for the costs or receives the benefits.